2017
DOI: 10.1080/15321819.2017.1350706
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of CD4 cell count among HIV-infected individuals in Lagos, Nigeria

Abstract: Human immunodeficiency virus (HIV) infection leads to progressive loss of CD4 T cells. Antiretroviral therapy has been able to inhibit this process, resulting in significant level of immune recovery and function. Our aim is to investigate the dynamics of CD4 recovery among HIV patients in Lagos, Nigeria. A total of 213 HIV-positive individuals were enrolled between October 2007 and May 2008, and followed up for 9 months based on CD4 count. CD4 analysis was done by flow cytometry at enrollment and after every 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Motayo et al [ 16 ] showed that the earlier the HAART starts, the faster the virus levels fall and the immune system rebuilds. Our results were consistent with these reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Motayo et al [ 16 ] showed that the earlier the HAART starts, the faster the virus levels fall and the immune system rebuilds. Our results were consistent with these reports.…”
Section: Discussionmentioning
confidence: 99%
“…e response variables in this study were the CD4 + cell count increase. Based on the reported risk factors [14][15][16][17][18] and data collected in this study, the predictor variables that seemed to affect the CD4 + cell counts were the following: gender, body mass index (BMI), age at follow-up, duration from HIV diagnosis to HAART start, duration of HAART, transmission route, WHO clinical stage, follow-up times, co-trimoxazole preventive therapy (CPT), HAART options, HAART replacement, creatinine, hyperlipidemia, liver function impairment, and anemia.…”
Section: Patients and Study Designmentioning
confidence: 99%
See 1 more Smart Citation